Malaya's first year at the United Nations as reflected in Dr Ismail's reports home to Tunku Abdul Rahman - Tawfik Ismail; Ooi, Kee Beng (Institute of Southeast Asian Studies, 2009)
Dr Ismail's writings and speeches, and his letters to the Tunku, covering a variety of foreign policy issues, are a valuable asset in understanding the unique role he played in the nation's history. He was without doubt the primary architect of Malayan (Malaysian) Foreign Policy. - Tengku Tan Sri Dato' Seri Ahmad Rithauddeen, Former Foreign Minister of Malaysia Not only was Dr Ismail Abdul Rahman Malaysia's first ambassador to the United States and permanent representative to the United Nations, he was also Foreign Affairs Minister in 1959-60. Later, as long-time Home Affairs Minister, Deputy.